Geo-Mechanical Performance Of Controlled Low Strength Materials With GGBS, Fly Ash, And Bagasse Ash As Cement Replacements (International Journal of Environmental Sciences, 2025)
The construction sector generates substantial quantities of industrial by-products such as quarry dust and hollow block powder, which present significant environmental and logistical challenges due to their fine particle nature and limited storage options. While previous research has explored the reuse of such materials in concrete, bricks, tiles, road base layers, and soil stabilization, their application in the development of Controlled Low Strength Materials (CLSM) also referred to as flowable fills remains underutilized.CLSM is a highly flowable, self-compacting, non-structural backfill material composed primarily of fine aggregates, cementitious binders, water, and industrial wastes. Conventionally, river sand is employed as the fine aggregate due to its favourable geotechnical characteristics. However, the escalating scarcity and environmental cost of river sand necessitate the adoption of sustainable alternatives such as quarry dust. In parallel, the high carbon footprint of Portland cement has encouraged interest in supplementary cementitious materials (SCMs) like Ground Granulated Blast Furnace Slag (GGBS), Fly Ash (FA), and Bagasse Ash (BA), which offer promising potential for partial cement replacement in CLSM.This study experimentally evaluates the flowability and compressive strength of CLSM mixes incorporating varying proportions of GGBS, FA, and BA as cement substitutes, with quarry dust as a full replacement for natural sand. The objective is to determine the optimal combinations of waste-derived materials that can maximize cement replacement while maintaining or enhancing performance characteristics, thereby supporting environmentally responsible and cost-effective backfill solutions. The research contributes to the advancement of sustainable construction materials in line with Indian practices and standards, with potential applicability in infrastructure, trench reinstatement, and geotechnical rehabilitation projects.